The systematics of the Mexican populations of Macrobrachium digueti (Bouvier, 1895) (Decapoda: Caridea: Palaemonidae) - García Velazco, Humberto; Maeda Martínez, Alejandro M.; Obregón Barboza, Hortencia; Campos Torres, Oliva; Murugan, Gopal (2017)
ABSTRACT Macrobrachium digueti (Bouvier, 1895), an amphidromous shrimp with unequal chelae, was described from Mulegé River in Baja California Peninsula, Mexico. A controversy on the morphological identity of M. digueti started six decades ago. Some authors point out that the redescription given in 1952 by L. Holthuis in his important revision of the Palaemonidae of the American continent does not correspond to Bouvier’s species. A controversy also exists on the taxonomy of the species because morphological and molecular studies have indicated great similarity of M. acanthochirus Villalobos, 1967 and M. michoacanus Nates and Villalobos in Villalobos Hiriart & Nates Rodríguez, 1990 with M. digueti (sensu Bouvier), suggesting their synonymy with the last species. We review the systematics of the Mexican populations of the putative M. digueti (Bouvier, 1895) consisting by individuals with unequal chelae, a carpus shorter than the merus and scarce pubescence on the palm and cutting edges of the fingers of the larger male second pereiopod. Extensive field surveys of the species of Macrobrachium Spence Bate, 1868 were made along the Pacific slope of Mexico, from the Baja California Peninsula in the north to Guerrero state in the south, an area that covered the type localities of the three nominal species. Results of the morphological revision and molecular genetic analyses with fragments of the mitochondrial genes 16S and COI confirmed the morphological identity of M. digueti as described by Bouvier and indicate that this entity is a morphologically plastic genetic species with a disjunct distribution along the peninsula and the Pacific mainland. Our study also confirms that M. acanthochirus and M. michoacanus are junior synonyms of M. digueti. Implication of present findings on the amphiamerican species groups of Macrobrachium is discussed. Key Words: Baja California Peninsula, digueti subgroup, olfersii subgroup, Pacific slope, phylogenetics, systematics, 16S gene, COI gene